PERBANDINGAN METODE BAGIAN DENGAN METODE KESELURUHAN TERHADAP FOREHAND DRIVE TENIS MEJA - Aditya Wiguna; Surisman Surisman; Ade Jubaedi (JUPE (Jurnal Penjaskesrek), 2016)
This study aimed to compare the section method training and the overall training methods to the learning achievement of table tennis forehand drive. This type of research was a comparative experimental or quasi-experimental. Population were 20 students. Data collecting technique was using a